Adventitious agent detection methods in bio-pharmaceutical applications with a focus on viruses, bacteria, and mycoplasma. (October 2021) - Morris, Caitlin; Lee, Yong Suk; Yoon, Seongkyu
Graphical abstract: Highlights: Adventitious agent detections are important due to regulatory affair and versatility. Novel biosensors present avenues for real-time adventitious agent detection. Real-time detection methods could be translated into gene therapy platforms. Abstract : Adventitious agents present significant complications to biopharmaceutical manufacturing. Adventitious agents include numerous lifeforms such as bacteria, fungi, viruses, mycoplasma, and others that are inadvertently introduced into biological systems. They present significant problems to the stability of cell cultures and the sterility of manufacturing products. In this review, detection methods for bacteria, viruses, and mycoplasma are comprehensively addressed. Detection methods for viruses include traditional culture-based methods, electron microscopy studies, in vitro molecular and antibody assays, sequencing methods (massive parallel or next generation sequencing), and degenerate PCR (polymerase chain reaction). Bacteria, on the other hand, can be detected with culture-based approaches, PCR, and biosensor-based methods. Mycoplasma can be detected via PCR (including specific kits), microbiological culture methods, and enzyme-linked immunosorbent assays (ELISA). This review highlights the advantages and weaknesses of current detection methods while exploring potential avenues for further development and improvement of novel detection methods. Additionally, a brief evaluation of the transition of these methods into the gene therapy production realm with a focus on viral titer monitoring will be presented.